Education Financing Policy : Implementation and Impact in Madrasah Aliyah - Hendrianto Hendrianto; Noza Aflisia; Soleha Soleha (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This research analyzed the implementation of education financing at MA Nurul Haq Semurup as well as the consequences and impacts of these policies on Sharia economy, educators and education personnel, madrasah environments, learning activities, and students.Design/Method/Approach: This research use descriptive qualitative approach. Sources of data came from the principal and teacher of MA Nurul Haq Semurup by using a research instrument in the form of closed interviews. The data obtained is then processed by stages of understanding the substance of the education financing standards contained in government policies and scientific articles, analyzing the results of interviews, analyzing the consequences and impacts of financing policies, as well as verifying and drawing conclusions.Findings: The results showed that MA Nurul Haq Semurup education financing was carried out in two ways, namely investment costs focused on financing learning facilities and human resource development, and operational costs focusing on educators' salaries and education personnel, student activities, consumables, indirect education, power subscriptions and services. The management of madrasah financing implemented has an impact on Sharia Economy (muamalah avoids Maysir, Gharar, Haram, and Riba), improving the competence of educators and education personnel, cleanliness and comfort of the madrasah environment, harmony between fellow madrasah personnel, systematic, measurable, and orderly madrasah governance, learning activities become interesting, meaningful, effective, and efficient, the spirit of leadership, independence, and discipline of students is formed, and students gain theoretical and practical learning.Originality/Values: The contribution of this research can provide valuable information related to education financing and become a reference of choice for other schools in the expenditure costs that have been set by the government and do not ignore the provisions in sharia economy.